Analisis Pengaruh Tingkat Spiritual Peserta Didik terhadap Kecanduan dalam Penggunaan Media Sosial pada Sekolah Menengah Atas - Ummah, Rohmatul; Kurniawan, Muhammad Bagus (Islamic Education Department, Islamic University of Majapahit (Universitas Islam Majapahit) Mojokerto, Indonesia, 2024)
Social media addiction is increasingly a concern because of its great potential to affect aspects of the life of the individual himself, including on the spiritual dimension of a person. This study aims to examine the relationship between social media addiction and spiritual level in students of Al-Qur'an An-Nawawiy High School. The results of the study showed that there was a significant relationship between the two variables, namely social media addiction and the spiritual level of students. Students who are more addicted to social media tend to have lower spiritual levels. However, it should also be emphasized that this is not the main factor, there are different factors behind each individual. These findings underscore the importance of awareness in the balanced use of social media to maintain spiritual balance in adolescents, especially students in religious education environments. This research contributes to the understanding of the impact of social media on the spiritual aspect, as well as provides a basis for the development of Steps taken to appropriately influence the situation in the context of religious education.